2012
DOI: 10.1080/02602938.2010.515012
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus written assessments: a test of student performance and attitudes

Abstract: Student performance in and attitudes towards oral and written assessments were compared using quantitative and qualitative methods. Two separate cohorts of students were examined. The first larger cohort of students (n = 99) was randomly divided into 'oral' and 'written' groups, and the marks that they achieved in the same biology questions were compared. Students in the second smaller cohort (n = 29) were all examined using both written and oral questions concerning both 'scientific' and 'personal development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(135 citation statements)
references
References 4 publications
8
117
2
8
Order By: Relevance
“…As for assessment methods which are perceived to test understanding over memory, oral examination is perceived by our students to be the method which most dominantly assesses understanding, followed by closed-book examination. Interestingly, this finding resonates with some of the research on oral assessment where this method is found to be beneficial for students in terms of engagement with the subject being studied (Huxham, Campbell and Westwood 2010), and where it is perceived by students to require deep understanding (Joughin 2007). The assessment method perceived to test understanding the least is multiple choice questions.…”
Section: Research In Mathematics Educationmentioning
confidence: 52%
“…As for assessment methods which are perceived to test understanding over memory, oral examination is perceived by our students to be the method which most dominantly assesses understanding, followed by closed-book examination. Interestingly, this finding resonates with some of the research on oral assessment where this method is found to be beneficial for students in terms of engagement with the subject being studied (Huxham, Campbell and Westwood 2010), and where it is perceived by students to require deep understanding (Joughin 2007). The assessment method perceived to test understanding the least is multiple choice questions.…”
Section: Research In Mathematics Educationmentioning
confidence: 52%
“…However, these students believed that oral examinations were more important than written tests for evaluating students' achievement of learning outcomes. In a similar study that compared students' performance on and attitudes toward oral and written assessments, Huxham, Campbell, and Westwood (2012) stated that "oral assessments may be more inclusive than written ones and that they can act as powerful tools in helping students to establish a 'professional identity'" (p. 125).…”
Section: International and Arabic Studies Of Pre-service Teachers' Prmentioning
confidence: 99%
“…In addition, oral examination better performed by emotional students rather than reserved and introverted ones, as it favors 'the extravert and confident student' [17]. These requirements, along with time consumption and lack of 'abstract reasoning' [7]in taking oral exam are looked upon as drawbacks.…”
Section: Theorymentioning
confidence: 99%
“…Oral exam is said to be old but certainly a "traditional practice in some areas of academic life" [7].…”
Section: Theorymentioning
confidence: 99%